Promoting Positive Youth Development Through Outdoor Physical Activity As An Alternative To Growing Life Skills; Narrative Literature Reviewer - Asep Ridwan Kurniawan; Komarudin Komarudin; Amung Ma'mun; dedi Iskandar (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Outdoors is one of the educational and recreational media that is expected to be able to bring out creativity and stimulate someone to be able to control their emotions about uncertainty over achieving goals in life. The method in this research is descriptive qualitative and narrative literature review. Data collection techniques using library research. Types of data using textual or conceptual. Aspects of analysis include definitions, concepts, views, thoughts and arguments. The source of data in this research is secondary data and refers to life skills or the term '5C' (Competence, Confidence, Character, Connections, Compassion/ Caring) in the development of strength-based youth as contained in the positive youth development program. (Lerner et al., 2005; Lerner et al., 2015) Research result; relation to outdoor physical activity as an alternative to fostering life skills through positive youth development programs that structured and unstructured outdoor recreational experiences can foster self-concept and enhance the development of motor skills and academic achievement as well as bring about competence and increased self-efficacy. In conclusion, outdoor experiences during adolescence can develop life skills that last a lifetime.